Intelligent interaction tests suite generator for iot testing - Nasser, Abdullah; Kamal Zuhairi, Zamli; Alsewari, Abdulrahman A.; Rassem, Taha H. (2021)
Typical Internet of Things (IOT) applications consist of large heterogeneous components. In order to ensure free-of-bug integration, there is need for testing all possible combinations (i.e., causing combinatorial explosion problem). Testing all possibilities is practically impossible owing to resource and time constraints. In order to address these issues, t-way testing approach has been adopted to minimize the tests systematically.